Tetrachloroethylene Removal Rate from Aqueous Solutions by Pumice Doped with Copper: An Evaluation of the Effect of pH - Ali Almasi; Mohammad Soltanian; Fateme Asadi; Parvin Nokhasi; Kazem Godini; Mitra Mohammadi; Ghasem Azarian; Ahmad Mohammadi (Hamadan University of Medical Sciences, 2016)
Tetrachloroethylene (TCE) is a chlorinated aliphatic hydrocarbon, used in many industries. Effective and efficient treatment of industrial wastewater, containing TCE, is one of the environmental requirements. The purpose of this study was to determine the role of alkaline environments in TCE removal rate from aqueous solutions, using copper-doped pumice. This experimental study was performed, using granulated pumice stones with a mesh 4 (8.4 mm) in alkaline conditions; the samples were coated with copper. Copper-doped pumice was prepared as a bed at doses of 1, 2, and 3 g/L; the study was performed at pH ranges of 3, 7, and 11. Based on the results, copper-doped pumice showed good efficacy in TCE removal; in addition, its performance increased in alkaline conditions. Therefore, use of this stone for the treatment of wastewater, containing TCE, is effective due to its availability and low cost. Besides, it can be considered a good option, given its high efficiency in the absorption process.